THE COMPARATIVE ANALYSIS OF STUDENTS’ DEPENDENCE ON THE TEACHER AT HIGH SCHOOL AND UNIVERSITY ESTABLISHMENTS - G‘afforova Asila Kamol qizi; Khasanova Yulduz Mukhtor kizi (Bright Mind Publishing, 2025)
This research focuses on evaluating student autonomy and the teacher-student relationship in Uzbekistan. Understanding students’ dependency on teachers is essential for improving the effectiveness of lesson planning and fostering independent learning. The study aims to clarify the level of student dependency and provide a structured approach to gradually developing learner independence. While similar studies have been conducted by scholars such as Zimmerman, B. J., and Quin, D., there has been limited research in Uzbekistan on this topic. Many students struggle with becoming independent learners when transitioning to university, highlighting the need for a structured approach to autonomy development. While scholars like B. Zimmerman and D. Quin have explored self-regulated learning and autonomy in Western contexts, there appears to be limited localized research on how Uzbek students adapt to the demands of independent learning at the university level. The primary objective of this study is to analyze student autonomy and propose effective classroom strategies that support students in adapting to independent learning. To achieve this, the research employs both qualitative and quantitative methods, including surveys and interviews. The findings will contribute to creating a more student-centered educational environment that gradually reduces reliance on teachers while enhancing self-regulated learning skills.
Keywords: Student autonomy, self-regulation, time-management, IELTS, TESOL, TKT.